Strategic Direction of a Local Government Unit-Funded College in the Philippines - Biray, Ersyl T.; Santos, Jr., Felix G. Delos (Future Science / FSH-PH Publications, 2025)
is descriptive study aimed at determining the status of a local col-lege in Aklan, Western Visayas and chart its strategic direction. Stakeholders composed of college students, parents, village offi-cials, business owners, school personnel, local government em-ployees, service providers such as boarding house owners, drivers, and graduating high school students provided data using a vali-dated researcher-made survey questionnaire guided by the prin-ciples of SWOT analysis. Results revealed that the strengths of the college include its creation through a municipal ordinance, pres-ence of a vision, mission, and goals, its strategic location, updated curricular programs, and the presence of a development plan. Its weaknesses are difficulties in recruitment and retention of faculty, integration of sustainable practices, limited space for expansion, minimal funding resources, and embracing of cultural diversity. The opportunities are possibility for expansion of academic pro-grams, marketing and branding strategy, attraction of diverse stu-dents, internship and job placement opportunities in the tourism island, innovative research, and resource allocation for student services. However, threats identified include competition from other academic institutions, natural disasters and global health crises, economic fluctuations and budget cuts, changes in govern-ment funding regulations, and demographic shifts and changes in the labor market. A strategic direction for the college was crafted focusing on the areas of instruction, research, community en-gagement, production, internationalization, and administration where goals, objectives, strategies, programs, projects, and activi-ties for the institution were underscored. Presentation of the pro-posed plan to the school administrators, stakeholders, and LGU officials was recommended.